Spirituality, mental health, and social support: a community approach - Jakob, Beate; Weyel, Birgit (Studies in spiritual care, 2020)
Frontmatter -- Foreword -- Contents -- Introduction -- Does Faith Heal? -- Religion and Health from the View of Psychology of Religion -- Depression and Spirituality/Religion -- Depression and Pastoral Care from the Viewpoint of Pastors in Germany -- What Motivates Volunteers in Congregations to Take Care of People with Mental Disorders? -- Is Faith a Source of Strength? Do Congregations Offer Support? -- Spirituality, Congregational Support, and Mental Health: The Example of Depression -- Mental Health and Mental Disorders: Knowledge, Perceptions, and Attitudes towards People with Mental Diseases -- Global Mental Health -- Promoting Mental Health at a Congregational Level -- “Nayi Roshni” – “New Light” for People Suffering from Mental Disorders -- Contributors -- Bibliography -- Online Sources -- Index
Keywords: Konferenzschrift -- 2016 -- Tübingen; Pastoralpsychologie; Religionspsychologie; Spiritual Care; Psychische Gesundheit; Religiosität; Spiritualität